Henry and Mudge and the funny lunch : the twenty-fourth book of their adventures - Rylant, Cynthia; Bracken, Carolyn (New York, NY : Scholastic Inc., 2004)
Mudge looks forward to the Mother's Day surprise that Henry and his father cook up for Henry's mother.
G4
Keywords: Dogs -- Fiction; Mother's Day -- Fiction; Fathers and sons -- Fiction; Food -- Fiction